Realistic scenarios of environmental disturbance lead to functionally important changes in benthic species-environment interactions. (September 2019) - Dolbeth, M.; Crespo, D.; Leston, S.; Solan, M.
Abstract: Changes in community structure concurrent with environmental forcing often form a precursor to changes in species diversity, and can have substantive consequences for ecosystem functioning. Here, we assess the effects of altered levels of evenness that are representative of different levels of eutrophication and changes in salinity associated with altered precipitation patterns, on the mediation of nutrient release by sediment-dwelling invertebrate communities. We find that an adjustment towards a more even distribution of species corresponds with an increase in sediment particle reworking that, in general, translates to increased levels of nutrient release. This response, however, is dependent on the functional role of each species in the community and is influenced by concomitant changes in salinity, especially when salinity extends beyond the range typically experienced by the community. Overall, our findings highlight the dynamic nature of species contributions to functioning and reinforce the importance of understanding when, and how, the mechanistic basis of species-environment interactions are modified as the influence of abiotic and biotic factors flex under periods of directional forcing. Highlights: The effect of benthic communities' altered evenness and salinity change was evaluated. Higher evenness generally led to an increase in bioturbation and nutrient release. Results were highly dependent on each species functional role in the community. Salinity levels beyond those typical encountered alter evenness-function relations. The magnitude and direction of changes in functioning is context dependent.